Functional characterization of 21 CYP3A4 variants on amiodarone metabolism in vitro. (2nd January 2019) - Yang, Cheng-Cheng; Zheng, Xiang; Liu, Teng-Hui; Wang, Chen-Chen; Tang, Peng-Fei; Chen, Zhe; Zhang, Bo-Wen; Fang, Ping; Hu, Guo-Xin; Cai, Jian-Ping
Abstract: 1. Cytochrome P450 3A4 (CYP3A4) is an important member of the cytochrome P450 enzyme superfamily, with 33 allelic variants reported previously. Genetic polymorphisms of CYP3A4 can produce a significant effect on the efficacy and safety of some drugs, so the purpose of this study was to clarify the catalytic characteristics of 22 CYP3A4 allelic isoforms, including 6 novel variants in Han Chinese population, on the oxidative metabolism of amiodarone in vitro . 2. Wild-type CYP3A4*1 and other variants expressed by insect cells system were incubated respectively with 10–500 μM substrate for 40 min at 37 °C and terminated at −80 °C immediately. Then these samples were treated as required and detected with ultra-performance liquid chromatography-tandem mass spectrometry used to analyze its major metabolite desethylamiodarone. 3. Among the 21 CYP3A4 variants, compared with the wild-type, the intrinsic clearance values ( V max / K m ) of two variants were apparently decreased (11.07 and 2.67% relative clearance) while twelve variants revealed markedly increased values (155.20∼435.96%), and the remaining of seven variants exhibited no significant changes in enzyme activity. 4. This is the first time report describing all these infrequent alleles for amiodarone metabolism, which can provide fundamental data for further clinical studies on CYP3A4 alleles.